Faktor Kualitatif Service-Profit Chain dalam Bisnis Franchise Restoran - Ireene*, Ireene (Universitas Syiah Kuala, 2023)
Understanding the factors that can influence business success may contribute to improving the food and beverages business concept, which has a large market potential in Indonesia. The factors that are of concern in this research are qualitative factors, based upon the idea in the service-profit chain theory. Research problem of this article is